The First Negotiations of the Delegation of the Republic of Armenia in Constantinople (June, 1918) - Petrosyan, Gegham (YSU Journal of International Affairs, 2022)
The makes a detailed focus on the complex and difficult diplomatic, strategic and tactical activities of the Armenian delegations to Constantinople and Berlin. Particular attention has been paid to the fact that the Armenian diplomats were making attempts to find a solution to the Armenian Question in the complex and difficult realities of geopolitical, economic and diplomatic contradictions and conflicts of interest between the states of the Central Powers, in particular Ottoman Turkey and German Empire. Particular attention has been also paid to the first talks of the Armenian delegation (chairman Av. Aharonyan) in Constantinople with the Grand Vizier of the Council of Ministers of Ottoman Turkey Talaat and Minister of War Enver Pasha.The article analyzes geopolitical factors, under the influence of which the first diplomatic visit of the Armenian delegation and negotiations with the Minister of War of Ottoman Turkey Enver Pasha were held. Particular attention has been paid to the fact that during the ongoing Armenian-Turkish diplomatic negotiations in Constantinople, the Ottoman Empire diligently continued discussions on creating a military-political union with the Republic of Armenia. In this regard, in July of 1918, German Empire demanded from its ally Ottoman Turkey to stop negotiations on the formation of this union on the following grounds. The Ottoman Empire cannot sign pacts and agreements separately with other countries without the mutual consent of the four allied states.
Keywords: Republic of Armenia; Quartet Union States; Germany; Turkey; Austria-Hungary; Hamo Ohanjanyan; Avetis Aharonyan; Taleat; Enver; Bersendorf; Mukhtar Bey